Trauma-Sensitive Practices in Health Education. Issue 9 (21st November 2020) - Wynard, Tammy; Benes, Sarah; Lorson, Kevin
Abstract : Two of the most important aspects of a health education teacher's work are to meet the needs of all students in their classes and to create a safe space in which those students feel supported and valued. This charge often brings to mind ensuring safe spaces for students related to aspects of their identity, such as their gender identity, sexuality, race/ethnicity, religious beliefs, or ability. While health educators must continue to address these, current evidence reveals that trauma is another aspect of students' experiences that we must recognize, acknowledge, and respond to in practice. Adverse Childhood Experiences (ACEs) is a term used to describe a range of potentially traumatic events such as abuse and neglect, but also untreated caregiver mental illness and household violence. ACEs have been linked to risky health behaviors, chronic health conditions, low life potential, and early death. The effects of ACEs and toxic stress may also impact the way students engage and behave in school. Health educators must be knowledgeable about ACEs and be equipped with strategies to ensure that they are implementing trauma-sensitive practices. This article provides an overview of key understandings about ACEs and trauma and describes approaches for trauma-sensitive practice in the health education classroom.